Validez de la bioimpedancia para estimar la composición corporal de mujeres entre los 18 y 40 años (2014)
ABSTRACT: The application of bioimpedance to estimate body composition in Colombia has increased in the last years. Objective: To validate bioimpedance equations to assess fat mass percentage (%FM) in women from Medellín-Colombia. Materials and methods: This is a cross sectional study with a sample of 52 women 18 to 40 years old. The %FM was assessed by the reference method hydrodensitometry and by hand-to-feet bioimpedance with the equations of Sun and Kotler, and feet-to-feet bioimpedance with a Tanita scale. Results: The %FM estimated by Kotler (31,9±6,0) and Tanita (25,6±6,1) were different (p<0.001) from hydrodensitometry (29,6±5,3). These techniques showed low agreement with the reference method, Kotler (Bland-Altman: -2,3 IC95%: -10,9; 6,1) and Tanita (BlandAltman: 4.0 IC95%: -6,3; 14,3). The %FM estimated by the Sun equation was similar to hydrodensitometry (29,6±5,3 Vs. 28,6±5,2, p=0,098). However, this equation showed low agreement with this method (Bland-Altman: 0,9 IC95%: -7,1; 9,0). Conclusions: The hand-to-feet bioimpedance with the Kotler equation and feet-to-feet bioimpedance with Tanita scale were not valid to assess the %FM of this specific population of women. The hand-to-feet bioimpedance with the Sun equation estimated accurately the average group of %FM, but it lacked of validity to assess the individual %FM in this population.